Perbedaan Penggunaan Toritatejoshi ‘Dake’ Dan ‘Bakari’ Dalam Novel Sakura House Karya Shizuko Toudou - Novianti, Nalti; Windriani, Yessie (Lingua Cultura, 2010)
An individual who only has little knowledge on grammar may use nouns, verbs, and adjectives in Japanese easily this is not the case with particles. Particles cannot be replaced or used at whim. This is the case with the particles â€˜dakeâ€™ and â€˜bakariâ€™. These particles in Bahasa Indonesia language have the same meaning with â€œhanyaâ€. This article analyzes particles â€˜dakeâ€™ and â€˜bakariâ€™ to determine the difference of the two particles. Source of data is the novel Sakura House by Toudou Shizuko and theory from Tomita Takayuki. Based on the analysis it is found that from the four functions of dake only three are found and from the seven functions of bakari only three functions are found. The authors conclude that differences in the two particles are present on several different functions that have both particle and that the bakari may not follow potential words, while dake can. In this study, the author uses descriptive analytical method and literature review.Â